PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA PERIMBANGAN TERHADAP BELANJA PEMELIHARAAN MELALUI BELANJA MODAL SEBAGAI VARIABEL INTERVENING PADA ANGGARAN PEMERINTAH DAERAH - Jalaluddin - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2009)
This research is aimed to provide empirical evidence of the influence of real regional income (PAD) and proportion funding toward expense of maintenance through capital expenditure in Aceh government regency/ city and town. Populations used in this research are 18 regencies, and 5 cities and town in Aceh government. Due to the consideration of the data availability, therefore the main targets of this study are 13 regencies and 4 cities and town. Data that used in this research is a secondary data that covers the total of real regional income (PAD), proportion funding, capital expenditure and expense of maintenance that included in revenue and expenditure budget district (APBD) realization of regency, city and town in Aceh government from 2006 to 2008. The data analysis method used in this research is path analysis method. Result of the research shows that simultaneously the allocation of real regional income (PAD) and proportion funding are influential to capital expenditure and expense of maintenance. But, partially, real regional income (PAD) has a negative influence to the expense of maintenance, whereas proportion funding and capital expenditure partially influential toward expense of maintenance.Â Keywords: real regional income (PAD), proportion funding, capital expenditure, expence of maintenance